Artificial perches increase seedling diversity and abundance in a degraded area in the Brazilian Midwest region (Research, Society and Development, 2020)
In the Midwest region of Brazil, forest fragments from the Atlantic Forest biome are disconnected from the landscape and with low resilience. Searching for potential restoration techniques, this study aimed to evaluate the interactions of artificial perches with some nucleation techniques, in order to confirm the hypothesis that the combination of these techniques increases the diversity of seeds and regenerants in the area. The experimental design was randomized in blocks, with five treatments and three replications. The restoration treatments included (1) control perches only; (2) perches with propagule collectors; (3) perches with brushwood transposition; (4) perches with food supply; and (5) perches with brushwood transposition and food supply. The experiment was conducted in a degraded area, which was previously colonized by pasture, in the surroundings of a forest remnant (reference ecosystem). After 365 days, the regenerants were identified (number of species and individuals). In the diversity of regenerants there was a significant increase with the interaction of more than one nucleation technique, highlighting the efficiency of the combination of artificial perches with collectors (T2) and brushwood transposition with food supply (T5). Based on the results it can be stated that the use of artificial perches combined with other nucleation techniques favors the recruitment of seedlings of zoochoric species and increases the seed bank through bird foraging. We believe that this technique is economically viable and has the potential for being used in restoration projects.